Coaching as an educator: Critical elements in a faculty development program - Lim, Sok Mui; Shahdadpuri, Ramesh; Pua, Ching Yee (Asia Pacific Scholar (Online), 2023)
Introduction: Coaching has gained acceptance in the education field as a way to enable learners to achieve their fullest potential. In the endeavor to set up a coaching ecosystem in our university, we started by equipping our educators with fundamental coaching skills and techniques. Our training workshop, Coaching As An SIT Educator, covers the key coaching competencies and is highly practice focused. Participants get hands-on skills practice using contextualised scenarios that are based on realistic academic, workplace and clinical placement settings. Methods: To address concerns on time-effectiveness, we adopt a solution-focused approach to coaching. We want to create a mindset shift for educators, from subject experts providing advice and solutions, to coaches asking powerful coaching questions that help students make discoveries and work towards their goals. We encourage our educators to engage students holistically by finding coachable moments in their daily student interactions. Results: Competency-based assessments are conducted to determine achievement of the learning outcomes, articulated by the knowledge, attitude, and demonstration of coaching skills with students. Assessments consist of a reflection, multiple-choice question (MCQ) quiz, and scenario-based coaching role plays. Participants achieved the learning outcomes as demonstrated from the assessments. Conclusion: The coach training workshop is the major pillar of our coaching initiative. Beyond the workshop, ongoing coaching development is supported through other activities and resources, including community of practice, coaching circle and knowledge repository. Opportunities for continuous learning and conversation platforms for sharing coaching experiences are part of the growing coaching ecosystem at SIT.